Independence - Divakaruni, Chitra Banerjee, 1956- (Gurugram, Haryana : HarperCollins Publishers India, 2022)
On decolonization and partition of the India.
Novel.
Also available as an e-book.
Keywords: India -- History -- Partition, 1947 -- Fiction